PENERAPAN KOMUNIKASI VERTIKAL DALAM MENINGKATKAN KUALITAS KINERJA PEGAWAI DINAS PERTAMBANGAN KABUPATEN KARIMUN - Haryati Yati (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
In an organization the success of communication is determined by the understanding of each individual involved in communication activities. Understanding is influenced by the clarity of the message, the way it is delivered, the situation and communication behavior. Vertical communication between superiors and subordinates in an organization is expected to establish good cooperation, so that it can lead to effective communication within an organization. The purpose of this study was to determine how the Application of Vertical Communication in Improving the Quality of Employee Performance in the Department of Mining of Karimun Regency. This study used descriptive qualitative method. The data obtained are interpreted and analyzed with theories that are relevant to this study which will then be described descriptively. Data collection techniques by distributing questionnaires, and observations. Data analysis uses statistic analysis. The population in this study were employees and honorary staff at the Karimun Regency Mining Service, which was divided into two categories consisting of staff and superiors (Head of Section, Head of Office, Secretary, and Head of Office). The sampling technique used is probability sampling. From the results of the presentation of data obtained in analyzing the discussion data, it can be seen that the application of vertical communication in improving the quality of performance of the Karimun Regency mining service employees results in the application of good vertical communication